The effects of various mouth rinses on enamel bond strength of a universal adhesive system - Ayar, Muhammet Kerim (Vojnosanitetski pregled, 2023)
Background/Aim. Although essential oil-containing mouth rinses have some advantages, it is not well-known what effects they have on the bond strength of the universal resin adhesives system to the enamel. The aim of the study was to evaluate the effect of essential oil-containing mouth rinses on the enamel bond strength of the universal adhesive system. Methods. A total of 96 bovine incisors were used in the study. The teeth were divided into four different groups according to the control group and three different mouth rinses: Group I (Control) – distilled water, Group II – Listerine Cool Mint (essential oil mouth rinse), Group III – Kloroben (0.12% chlorhexidine gluconate mouth rinse), and Group IV – Oxyfresh (0.05% sodium fluoride mouth rinse). Each group was divided into two subgroups according to the application mode of the universal adhesive (etch-and-rinse mode or self-etch mode) (n = 12). Mouth rinses were applied daily for 30 sec to the enamel surfaces for a month, and the samples were soaked in distilled water. After the shear bond strength (SBS) tests were performed with the universal test machine at a speed of 1 mm/min, the SBS data were statistically analyzed (p = 0.05). Results. Two-way ANOVA showed that the enamel bond strength of universal adhesive was not affected by mouth rinse and was significantly affected by the application mode. Conclusion. The use of essential oil-containing mouth rinses and other mouth rinses tested in the study is safe in terms of the quality of enamel bonding of the tested adhesive.
Keywords: adhesives; dental enamel; essential oils; mouthwashes